Control del entrenamiento deportivo en juegos Suramericanos Medellín 2010 (2012)
With the objective to determine if trainers that supported sportspeople in the South-American Games Medellin 2010, applied different tests in order to control sportsmen, a quantitative analysis was made which had a descriptive scope in which 93 trainers were surveyed (86 men and 7 women), aged in average 46 .1 years (±10 .2) with a minimum age of 24 and a maximum of 79. The average experience as trainer was of 20 .5 years (±9 .8); they came from 13 countries and were experts in 28 different sports. An intentional sample was taken, since the exact data of trainers attending the event was unknown. The technique used was the survey . In order to analyze the information an Excel program Windows 2007 was used. Results showed that 90 .3% of the consulted coaches, applied different control tests, 79 trainers employed field control, 45 lab control and 41 both ways. A tendency, that the participants trained by coaches from countries where control tests were applied (field and lab) achieved a higher number of medals was detected.